A Cross-Cultural Examination of Parental Knowledge of Concussion in Three Countries. Issue 8 (17th November 2021) - Moser, Rosemarie Scolaro; Friedman, Sarah; Hensel, Gustav Luke; Dubnov-Raz, Gal; Schatz, Philip
ABSTRACT: The aim of the present study was to examine and compare knowledge regarding concussion among parents of youth soccer players, ages 5–17, from the United States, Israel, and Sicily. Results revealed parents from the United States were more knowledgeable than Israeli and Sicilian parents and were more likely to have a previous history of concussion in their children, themselves, and their social contacts. The success of concussion education, programming, and legislation in the US may account for the greater knowledge of US parents and is reason to advocate for similar resources for youth athletes internationally.